Ensino profissionalizante e estado militar: (re)articulação por meio dos Polivalentes (Uberlândia, MG, 1971-1980) - Resende, Luciana Araujo Valle de (2011)
This study deepened the knowledge about the Polyvalent State School Guiomar de Freitas Costa, located in Uberlândia (MG), in the period between the years 1971 and 1980. The Polyvalent Schools rose in a period of great economic euphoria, caused by an industrial surge which demanded qualified labor and that the country, by the existing educational conditions, could not supply. The formation of technical laborers to act in the productive sectors of agriculture, industry and commerce was pressing. The major questions that moved this study were: in which context this school was created and how it operated in its early years? Who were its students and which repercussions this education had on their formation and subsequent professional performance? The search for answers for these questions contemplated, methodologically, research of institutional documents in the County Public Archives and at the Regional Superintendence of Education in Uberlândia, bibliography research and, lastly, interviews with students and professional alumni of the school. The Polyvalent Schools, using as guide line of schooling, to link theory and practice, structured their curricula to offer a general formation together with the vocational one, with courses covering general instruction as well as agricultural, industry, commercial and home economics practices. It can be perceived, then, that the Polyvalent State School Guiomar de Freitas Costa, as well as the other Polyvalent Schools, started its work in a different manner in respect to the education proposal and quality. The union of these differentials attracted to the institution a public which, in its majority, did not share its pre-professional objectives, configuring one of its contradictions. This enterprise, regardless of the great financial investment received and the expectations risen, with the decline of the law that constituted them the Law nº 5,692/71 also had its proposal and installed activities an ephemeral duration.